Faktor-Faktor yang Mempengaruhi Pemilihan Strategi Bisnis Rumah Sakit - Huriyah Huriyah (Jurnal Akuntansi dan Bisnis, 2004)
In the face of the severe business competition, an organization should own thespecific strategy that entails all aspects of the organization operation as the key todevelop the competitive advantage. The existence of the comprehensive strategysustains the organization to achieve the success of anticipating the fast changingenvironment. This research aims at evaluating whether the common strategy used toachieve the competitive advantage by a profit-oriented company can also be used by ahospital. This research analyses the factors influencing the types of the businessstrategy: the environment uncertainty, the professional level, the informationtechnology need. The data were gathered by distributing questionnaires to topmanagers of private hospitals in Java. The number of returned questionnaires was 32.Logistic regression was used to test hypothesis. The results shows that informationtechnology need had an impact on the type of the business strategy but do not supportthe argument that the environment uncertainty, the professional level affected the typeof the business strategy.